Nonalcoholic fatty liver disease: Diagnosis, pathogenesis, and management - Başaranoğlu, Metin; Örmeci, Necati (Turkish Journal of Gastroenterology, 2014)
Abstract Nonalcoholic fatty liver disease (NAFLD) is an umbrella term that covers both a relatively benign condition, which is simple steatosis, and nonalcoholic steatohepatitis (NASH). NASH is characterized by a chronic and progressive liver pathology that may progress to cirrhosis, end-stage liver disease, hepatocellular carcinoma, and liver transplantation. Despite the growing body of evidence, one of the important and unresolved problems is the pathogenesis of NASH. It might be a metabolic disturbance as a primary abnormality in NAFLD. Insulin resistance is at the center of these metabolic abnormalities. Then, hepatocyte injury might be induced by oxidative stress. This ongoing process progresses to NASH, even to cirrhosis in some patients. In addition to oxidative stress, possibilities for the next hit are lipid peroxidation, reactive metabolites, adipose tissue products, transforming growth factor-β1, Fas ligand, mitochondrial dysfunction, respiratory chain deficiency, and intestinal microbiota. Currently, there is no well-established and approved therapy. Recommendations are to improve existing co-morbidities, such as obesity, hyperlipidemia, or type 2 diabetes, and lifestyle modification with weight loss and exercise.